Frontier Computing Theory, Technologies and Applications (FC 2018) - Hung, Jason C.; Yen, Neil Y.; Hui, Lin.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents the proceedings of the 6th International Conference on Frontier Computing, held in Kuala Lumpur, Malaysia on July 3-6, 2018, and provides comprehensive coverage of the latest advances and trends in information technology, science and engineering. It addresses a number of broad themes, including communication networks, business intelligence and knowledge management, web intelligence, and related fields that inspire the development of information technology. The contributions cover a wide range of topics: database and data mining, networking and communications, web and internet of things, embedded systems, soft computing, social network analysis, security and privacy, optical communication, and ubiquitous/pervasive computing. Many of the papers outline promising future research directions. The book is a valuable resource for students, researchers and professionals, and also offers a useful reference guide for newcomers to the field.
Cloud, Ubiquitous, Pervasive, and High Performance Computing -- Dependable, Reliable and Autonomic Computing -- Wearable Computing, Mobile Web, and Smart Environment -- Algorithm, Model, and Framework Programming Languages -- Communication and Networking -- Database and Data Mining -- Big Data and Internet of Things -- Anticipatory Computing -- Web and Internet Computing -- Natural Language Processing Operating Systems -- Image Processing, Pattern Recognition, Multimedia Technology -- Embedded System and Software -- Geographical Information Systems/ Global Navigation Satellite Systems (GIS/GNSS) -- Intelligent Information & Database Systems -- Security and Privacy -- Social Web, Network, and Computing -- Social, Ethical & Other Issues of Networked World -- Software Design Patterns & Engineering -- Information/Business Management, and IT Policy -- Mobile and Ubiquitous Computing -- Modeling and Simulation -- Multimedia Systems and Services -- Integrating Technology in Real-World Environment -- Promising Topics in All Aspects of Information Technology, Science, and Engineering.
Keywords: Computational intelligence; Computer networks .; Multimedia systems; Electronic circuits; Computational Intelligence; Computer Communication Networks; Multimedia Information Systems; Electronic Circuits and Systems